PERAN LOGIKA DALAM TINDAKAN IMAN DAN RELEVANSINYA DALAM KEHIDUPAN KEKRISTENAN - Josep Tatang; Victor Deak; Shania Chukwu; Dona Sihombing (Journal of Industrial Engineering & Management Research, 2022)
Discussions on logic and faith are not new things among Christians which often lead to conflicts. Logic is a philosophy of correct thinking, a science of correct thinking and at the same time it is an art of correct thinking. On the other hand, the act of faith is a person's willingness to sacrifice himself for the sake of his faith. Man is created in the image of God and it can be seen in his ability to reason and think so that the act of maximizing reason or logic that has been given to us is one of our ways to glorify God. Logic plays its role in making decision whether to act or not to act on something including when someone makes a decision to act on his Faith. Logic can prevent fallacy in thinking coming from incorrect faith, therefore harmony in the use of logic in regard of action of faith is important. The purpose of this study is to examine the role of logic in the act of faith and its relevance in Christian life. Researchers use a combination research method of quantitative and qualitative research ones.